Financial Performance Segmentation Changes of Indonesian Insurance Companies Listed on Indonesia Stock Exchange (IDX) - Dewi, Puspita; Dzulqornain, Muhammad; Heikal, Jerry (Universitas Pahlawan Tuanku Tambusai, 2025)
The acquisition is one of the techniques for creating and preserving the firm's survival, especially if unforeseen circumstances occur that are averse to a company, such as in the insurance industry during the Covid-19 pandemic. This study examines the financial performance segmentation changes of Indonesian insurance companies listed on the Indonesia Stock Exchange (IDX) in the context of the Covid-19 pandemic's impact on the industry. Utilizing a quantitative research design, the research employs K-Means Clustering to analyse key financial performance indicators, including Debt-to-Equity Ratio (DER), Return on Equity (ROE), Net Profit Margin (NPM), and Risk-Based Capital (RBC) for the periods of December 2021 and December 2022. The findings reveal significant shifts in the financial health and risk profiles of these companies, highlighting the importance of robust financial metrics in acquisition strategies. The study further investigates the financial ratios for December 2023 to assess the outcomes of recent acquisitions, such as that of PT Lippo General Insurance Tbk by Hanwha Life, and whether these acquisitions have resulted in synergistic benefits. The insights gained from this research provide valuable implications for stakeholders, including potential acquirers and regulators, by enhancing their understanding of market dynamics and informing strategic decision-making in the evolving insurance landscape of Indonesia..